Characterization of immunoreactivity with whole-slide imaging and digital analysis in high-grade serous ovarian cancer - Tiina Jäntti; Satu Luhtala; Johanna Mäenpää; Synnöve Staff (Tumor Biology)
Ovarian cancer is the most lethal of gynecological cancers with 5-year survival rate of ca. 45%. The most common histologic subtype is high-grade serous carcinoma, which typically is presented with advanced stage and development of chemoresistance. Therefore, new treatment options, including immunotherapies, are needed. Understanding the features of the immune cell populations in the tumor microenvironment is essential for developing personalized treatments and finding predictive biomarkers. Digital image analysis may enhance the accuracy and reliability of immune cell infiltration assessment in the tumor microenvironment. The aim of this study was to characterize tumor microenvironment in a retrospective cohort of high-grade serous carcinoma samples with whole-slide imaging and digital image analysis. Formalin-fixed paraffin-embedded high-grade serous carcinoma tumor tissue samples (n = 67) were analyzed for six immunohistochemical stainings: CD4, CD8, FoxP3, granzyme B, CD68, and CD163. The stained sample slides were scanned into a digital format and assessed using QuPath 0.1.2 and ImageJ software. Staining patterns were associated with clinicopathological data. The higher numbers of intraepithelial CD8+, CD163+, and granzyme B+ immune cells were associated with survival benefit when analyzed individually, while high levels of both CD8+ and granzyme B+ tumor-infiltrating lymphocytes were an independent prognostic factor in the Cox multivariate regression analysis (median progression-free survival; hazard ratio = 0.287, p = 0.002). Specimens taken after administration of neoadjuvant chemotherapy presented with lower FoxP3+ tumor-infiltrating lymphocyte density (Fisher’s exact test, p = 0.013). However, none of the studied immunomarkers was associated with overall survival or clinical factors. Tumors having high amount of both intraepithelial CD8+ and granzyme B+ tumor-infiltrating lymphocytes showed better progression-free survival, possibly reflecting an activated immune state in the tumor microenvironment. The combined positivity of CD8 and granzyme B warrants further investigation with respect to predicting response to immune therapy. Neoadjuvant chemotherapy may have an effect on the tumor microenvironment and therefore on the response to immuno-oncologic or chemotherapy treatments.